RIPARIAN WATER RIGHTS - Salma, Marija (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
The paper offers analysis of a right to existential use of water resources (public waterways and water recipients) by owners of agricultural law located immediately next to these types of water resources. This right covers the right to drinkable water, livestock drinking water and basic irrigation without a use of special irrigation equipment. The right-holder of the listed types of the use of water resources is different from the right-holder of the general use of water resources. In the earlier case the right-holder is the owner of the riparian agricultural land. The holder of the general right of use may be any person, under equal terms, regardless of whether he owns agricultural or other type of land next to the waterway. The right of the riparian land owners differs from the general right of use because they enjoy priority over the right of use by other persons holding general rights of use over waterways. The water rights of riparian land owners overlaps with the general right of use in that it covers the use of water for existential needs. The rights of the riparian land owner are different from the so called special or commercial use of water resources (use of water and water power for commercial purposes, such as production of electrical power, etc.). The difference is that the rights of the riparian land owners is derived directly from the law, without the need for any action by the state organs (water resource permits) and is free of charge. On the other hand, the right to commercial use of public water resources is always based on water use permits or approvals and concession agreements and is associated with a fee payable to the owners of the public water resource.